Effect of spray and freeze drying on physico-chemical, functional, moisture sorption and morphological characteristics of camel milk powder. (December 2020) - Deshwal, Gaurav Kr; Singh, Ashish Kumar; Kumar, Devendra; Sharma, Heena
Abstract: This study investigated the changes in camel milk powder on spray and freeze drying by preparing spray dried whole camel milk powder (SDW), spray dried skimmed camel milk powder (SDS) and freeze-dried whole camel milk powder (FDW). All the powder variants showed significant changes (P < 0.05) in their composition, water activity and color values. Freeze dried powder (FDW) showed higher retention of calcium (15.33 g/kg) and iron (0.012 g/kg) while SDS possessed highest L* (94.83 ± 0.74) values. FDW sample had highest interstitial air (80.84 ± 0.66 mL/100 g), occluded air (119.47 ± 1.08 mL/100 g) and porosity (50.59 ± 0.56%) followed by SDS which was further reinforced by their SEM images. The water binding capacity was highest for FDW (5.21 g/g protein) and lowest for SDW which is attributed to highest porosity and presence of surface fat, respectively. Freeze-dried camel powder had porous sheet like structure while the spray dried samples were agglomerates of individual spherical particles. FTIR peak differences between whole camel milk powder samples (FDW and SDW) and skimmed powder sample (SDS) in wavenumber range 2850–3000 cm −1 was due to milk fat. Fitted with BET and GAB model, the moisture sorption isotherm showed lowest monolayer moisture content for SDW, thereby highlighting its better storage stability. Graphical abstract: Image 1 Highlights: Spray dried whole (SDW) and skimmed (SDS) camel milk powders were characterized. Freeze dried whole camel milk powder (FDW) had highest dispersibility & solubility. Reconstituted powders (10% solution) showed maximum heat stability at pH 6.8 to 7.0 FDW, SDW and SDS had porous, agglomerated and brain type structure, respectively. BET and GAB models showed highest monolayer moisture for SDS at 25 °C and 35 °C.